2021
DOI: 10.3390/ijerph18073512
|View full text |Cite
|
Sign up to set email alerts
|

Pathways Improving Compliance with Preventive Behaviors during the Remission Period of the COVID-19 Pandemic

Abstract: The COVID-19 pandemic poses a significant threat to people’s lives. Compliance with preventive behaviors, recommended by public health authorities, is essential for infection control. In the remission stage, one year after the initial COVID-19 outbreak in China, we advanced a moderated parallel mediation model of the link between risk perception and compliance with preventive behaviors as well as a serial mediation model of the link between optimism and compliance with preventive behaviors, explaining the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Previously, associations have typically been examined separately between risk group membership and adherence ( 12 , 15 , 16 , 43 ), risk (objective and subjective) and affective reactions such as anxiety, fear, or worry ( 18 20 , 22 , 23 ), as well as between such affective reactions and adherence to behavioral measures ( 14 , 23 , 25 ). Similar to initial research with a Chinese sample ( 26 ), our results show that COVID-19 threat mediates the effect of both risk group membership indicators on the examined preventive behaviors. This finding also corresponds to other studies on health decision making, which find a mediating effect of worry explaining the relationship between perceived risk and health behavior ( 44 46 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Previously, associations have typically been examined separately between risk group membership and adherence ( 12 , 15 , 16 , 43 ), risk (objective and subjective) and affective reactions such as anxiety, fear, or worry ( 18 20 , 22 , 23 ), as well as between such affective reactions and adherence to behavioral measures ( 14 , 23 , 25 ). Similar to initial research with a Chinese sample ( 26 ), our results show that COVID-19 threat mediates the effect of both risk group membership indicators on the examined preventive behaviors. This finding also corresponds to other studies on health decision making, which find a mediating effect of worry explaining the relationship between perceived risk and health behavior ( 44 46 ).…”
Section: Discussionsupporting
confidence: 84%
“…Several studies have also found relationships between anxiety, worry, fear, and behavior change or adherence to COVID-19 behavioral measures ( 14 , 23 , 25 ). Therefore, it stands to reason that individuals who perceive themselves at risk feel threatened by the virus, prompting them to adhere to behavioral measures, as supported by first evidence ( 26 ). Given the prior findings on the relation between being at risk and adherence, being at risk and anxiety, as well as anxiety and adherence in the context of COVID-19, we explore: first, whether individuals at risk of exposure to COVID-19 or severe COVID-19 infection adhere more often to COVID-19 behavioral measures and, second, whether perceived threat of COVID-19 mediates the relationship between risk group membership and adherence.…”
Section: Introductionmentioning
confidence: 96%
“…A systematic review of 38 international articles showed that the COVID-19 pandemic led to reductions in household food waste, improved cooking behaviors, and food consumption [ 47 ]. Other studies evaluating the effect of knowledge and/or perceived threat of COVID-19 found similar positive relationships with the adaptation of protective measures such as handwashing, social distancing, and hygiene rules [ 8 , 48 , 49 , 50 ]. Therefore, it is plausible that perception of the harm of COVID-19 and knowledge of associated risks and protective measures prompted the adoption of healthy behaviors, including the consumption of a healthy diet that contains nutrients reported to boost immunity and prevent inflammation such as vitamins B12, C, D, zinc, and iron [ 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 68%
“…Anxiety about contracting COVID-9 and death due to it may raise awareness about disease prevention and reduce the disease spread [ 34 ]. For example, patients with chronic diseases, who are anxious about contracting the infection, are likely to choose handwashing as a safety mechanism to control infection [ 35 ]. Conversely, those who reported depression had significantly poorer hand hygiene practices than those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first large-scale study to report an association between mental health problems and hand hygiene practices in Korean adults with HTN and DM during the COVID-19 pandemic. Many previous studies have emphasized the need for active mental health management to enable infection prevention behavior in patients with chronic diseases [ 32 , 33 , 35 ]. Taken together, these results suggest that the negative mental health of patients with non-communicable diseases (NCD) due to the impact of COVID-19 adversely affects healthy behavior.…”
Section: Discussionmentioning
confidence: 99%